Galectin‐3 expression in thyroid fine needle cytology (t‐FNAC) uncertain cases: Validation of molecular markers and technology innovation. Issue 5 (28th January 2013) - Papale, F.; Cafiero, G.; Grimaldi, A.; Marino, G.; Rosso, F.; Mian, C.; Barollo, S.; Pennelli, G.; Sorrenti, S.; De Antoni, E.; Barbarisi, A.
Abstract Thyroid cancer is not very common, accounting for 1–2% of all cancers, with a population incidence of about 0.004%. Currently, the ability to discriminate between follicular adenoma and carcinoma represents the major challenge in preclinical diagnosis of thyroid proliferative lesions. Better discrimination between the two would help avoid unnecessary thyroidectomy and save valuable resources. Over the years, galectin‐3 (Gal‐3) has been proposed as a diagnostic marker with varied success. In this paper, we used Environmental Scanning Electron Microscopy Immunogold Labelling (ESEM‐IGL) to investigate the expression of Gal‐3 on Thin‐Prep fine needle aspiration cytology (FNAC). We optimized the ESEM‐IGL method on thyroid cell lines (RO‐82 and FTC‐133) comparing our membrane Gal‐3 labeling data with Western blot. We evaluated 183 thyroid FNAC from Italian patients with a uncertain pre‐surgical diagnosis. ESEM‐IGL method marker sensitivity is 71.2%, while specificity is 53.3% and diagnostic efficacy is 61.2%. Our results confirmed that Gal‐3 expression is associated with situations of hypertrophy and/or cellular hyperproliferation, pathophysiological situations common both to adenomas and to thyroid carcinomas. The innovation of thyroid FNAC Thin‐Prep ESEM‐IGL shows the levels of Gal‐3 immunolabeling clearly, even through the individual cells of a thyroid nodule. However, Gal‐3 alone, as a molecular marker of thyroid cancer, can still have a limited application in pre‐surgery diagnosis. J. Cell. Physiol. © 2012 Wiley Periodicals, Inc.